THE ROLE OF GRADED READING MATERIALS IN TEACHING READING OF EFL LEARNERS - SHELLA MONICA (Sriwijaya University Learning and Education International Conference, 2016)
One of the priority purpose of teaching English as a foreign language to Indonesian people is thatthey can read in order to grasp the idea and to understand the book written in English. The ability toread is crucial for the students in reaching both the academic and society success. The successfulnessof teaching reading cannot be separated from the skill of selecting an appropriate reading material.By reading an appropriate reading material, the students can effectively expand their knowledge;train their brain to think and acquire new information and idea. This paper aimed at discussing therole of graded reading materials in teaching reading of EFL learners. A number of studies point outthat the L2 learners will feel motivated and enjoy in learning the language if the anxiety levels are aslow as possible. Graded reading material which is written in various levels of reading, meets theneeds of today’s language learners by maximizing reading opportunities in an enjoyable, relaxing andaccessible way.